Exploring learners’ experiences with mobile technology: Academic uses and barriers - Essafi, Mohamed; Belfakir, Latifa; Moubtassime, Mohammed (Edelweiss Applied Science and Technology, 2025)
In an increasingly digital era, mobile technology has become an integral part of our daily lives, permeating various aspects, including education. with their portable nature and wide range of functionalities, mobile devices offer new opportunities for learners to access information, collaborate with peers, and engage in interactive learning experiences. This article investigates university learners’ experiences with mobile technology, as well as their perceived barriers to such experiences in the context of English language learning. The study employs a mixed-methods approach, comprising surveys and interviews to investigate students’ practices and barriers related to using mobile technology for language learning. The quantitative stage involves a sample of 142 participants, while the qualitative stage focuses on a subset of 16 participants selected for representation and diversity. The findings show extensive reliance of students on their devices for on-campus and off-campus learning activities, including chatting with AI models, social networking, app-based learning, and watching course-related videos. Furthermore, several barriers pertaining to the device, the teacher, and the learner were identified as obstacles to the effective use of mobile technology for academic purposes. Overall, this study stresses the potential of mobile devices for language learning and offers valuable insights into how students use them. Language teachers and researchers can utilize these findings to maximize the benefits of mobile technology while mitigating its drawbacks.